Multiletramentos mediados pelo gênero relato pessoal em uma Turma de Jovens e Adultos - Matos, Virgínia Maria da Costa (2021)
The research entitled Multiliteracies mediated by the Gender Personal Report in a Class of Young People and Adults aimed to investigate practices of multiliteracies, in classes of young people and adults, mediated by the Personal Report. Multiliteracies with their multiple languages bring all the multiculturalism and multimodality linked to the texts that go around globalized societies (ROJO; MOURA, 2012; ROJO; BARBOSA, 2015). The research was based on the theoretical assumptions of the (DDT) Dialogical Discourse Theory (BAKHTIN and its Circle-1920), since they treat language as the basis of relationships and dialogical relations as a guarantee of plurality and the provocation of new ideas and their direct relationship with the alterity and responsiveness of social subjects.Therefore, the planning of pedagogical actions aimed at Youth and Adult Education (EJA) must promote the critical dialogue in order to minimize the difficulties on reading and writing brought throughout the history of this modality of education with so many specificities (ARROYO, 2014; FREIRE, 2017).The apprehension of linguistic knowledge according to the communicative situations proposed by the discursive domain of the Gender Personal Report can make possible, through discursive practices developed by the students in their oral/written productions, meaningful teaching and learning. Multiliteracies propose interactive learning, generating questions and the use of multiple languages in EJA classes, it can be an ally in the formation of a critical individual, active subject, performing his right as a citizen. Personal Report, originally an oral gender and situated in the discursive domain of youth and adults, was selected to anchor the planned workshops, which involved other discursive genders present in the students' daily lives and which aimed to analyze the situated uses of language, its purposes and intentions within EJA's social context. As for the methodological aspects: the research was developed in an EJA class of the night shift (second segment), in a school on the outskirts of Fortaleza. The teacher-researcher searched for teaching strategies starting from the application of a work plan composed of a sequence of five steps, when the students had the opportunity to develop their skills in a systematic way, taking part in a structured didactic process, in which there was respect for logic, learning rhythm and cognitive development of the class. The methodology used was based on the Critical-History Theory (SAVIANI, 2013) which proposes that school work should have as its primary element the cultural development and involve the understanding of the human historical-cultural reality produced by man himself, through his work over time. Based on a bibliographic material already published and with the building of a textbook, based on the proposal of a Teaching Work Plan (GASPARIN, 2015), at the end of the activities, the teacher-researcher verified, through the written productions developed by the students, that, as far as possible, there was significant learning and that the multi-learning practices could cause relevant changes in the teaching and learning of the mother tongue of young people and adults.